The Utility of a Brief Web-Based Prevention Intervention as a Universal Approach for Risky Alcohol Use in College Students: Evidence of Moderation by Family History - Neale, Zoe E.; Salvatore, Jessica E.; Cooke, Megan E.; Savage, Jeanne E.; Aliev, Fazil; Donovan, Kristen K.; Hancock, Linda C.; Dick, Danielle M. (Frontiers in Psychology, 2018)
Background: Alcohol use on college campuses is prevalent and contributes to problems that affect the health, emotional wellbeing, and academic success of college students. Risk factors, such as family history of alcohol problems, predict future alcohol problems, but less is known about their potential impact on intervention effectiveness. The purpose of this study was to examine the effect of an intervention implemented in a non-randomized sample of drinking and non-drinking college freshmen. Methods: Freshmen college students recruited for the intervention study (n=153) completed a web-adaptation of the Brief Alcohol Screening and Intervention for College Students (BASICS) at the start of spring semester. We compared their 30-days post-intervention alcohol initiation, number of drinking days (DAYS), drinks per occasion (DRINKS), maximum drinks in 24 hours (MAX24) and alcohol use disorder symptoms (AUDsx) to 151 comparison participants retrospectively matched on demographics and baseline alcohol use behaviors. We also tested baseline DRINKS, DAYS, AUDsx, MAX24, and parental family history (PFH) of alcohol problems as moderators of the effect of the intervention. Results: At follow-up, intervention participants had lower rates of AUDsx than comparison participants, especially among baseline drinkers. Among participants drinking 3+ days/month at baseline, intervention participants showed fewer DAYS at follow-up than the comparison group participants. BASICS was also associated with a decreased likelihood of initiation among baseline non-drinkers. PFH significantly interacted with treatment group, with positive PFH intervention participants reporting significantly fewer AUDsx at follow-up compared to positive PFH comparison participants. We found no evidence for an effect of the intervention on DRINKS or MAX24 in our analyses. Conclusions: Results suggest some indication that novel groups, such as non-drinkers, regular drinkers, and PFH positive students may experience benefits from BASICS. Although conclusions were limited by lack of randomization and short follow-up period, PFH positive and low to moderate drinking groups represent viable targets for future randomized studies.